Deficient IL-2 Produced by Activated CD56+ T Cells Contributes to Impaired NK Cell-Mediated ADCC Function in Chronic HIV-1 Infection - Xie, Zhe; Zheng, Jiajia; Wang, Yuya; Li, Dan; Maermaer, Tuohutaerbieke; Li, Yuantao; Tu, Jing; Xu, Qiang; Liang, Hua; Cai, Weiping; Shen, Tao (Frontiers in Immunology, 2019)
Background: Antibody-dependent cellular cytotoxicity (ADCC), which mainly mediated by natural killer (NK) cells, may play a critical role in human immunodeficiency virus type-1 (HIV-1) disease progression. However, the potential mechanisms that affecting NK-mediated ADCC response are still not well elucidated. Methods: Antigen-antibody complex model of Ab-opsonized P815 cells was adopted to induce a typical non-specific ADCC response. The capacities of HIV-1 specific NK-ADCC were measured by using the combination model of gp120 protein and plasma of HIV-1 elite controllers. The levels of plasma cytokine were measured by ELISA. Anti-IL-2 blocking antibody was used to analyze the impact of activated CD56+ T cells on NK-ADCC response. Results: IL-2, IL-15, IFN-α and IFN-β could effectively enhance the non-specific and HIV-1-specific NK-ADCC responses. Compared with healthy controls, HIV-1-infected patients showed decreased plasma IL-2 levels, while no differences of plasma IFN-α, IL-15 and IFN-β were presented. IL-2 production was detected from CD56+ T cells activated through antibody-dependent manner. The capability of NK-ADCC could be weakened by blocking IL-2 secretion from activated CD56+ T cells. Although no difference of frequencies of CD56+ T cells was found between HIV-1-infected patients and healthy controls, deficient IL-2 secretion from activated CD56+ T were found in chronic HIV-1 infection. Conclusions: The impaired ability of activated CD56+ T cells to secreting IL-2 might contribute to the attenuated NK cell-mediated ADCC function in HIV-1 infection.